2014
DOI: 10.1002/ana.24116
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and traumatic brain injury

Abstract: ObjectiveTraumatic brain injury (TBI) is a multifactorial pathology with great interindividual variability in response to injury and outcome. Mitochondria contain their own DNA (mtDNA) with genomic variants that have different physiological and pathological characteristics, including susceptibility to neurodegeneration. Given the central role of mitochondria in the pathophysiology of neurological injury, we hypothesized that its genomic variants may account for the variability in outcome following TBI.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Additionally, it is likely that multiple genes influence recovery and susceptibility to brain injury and one cannot study a single genetic polymorphism in isolation. For example, in a study of over 1000 European patients with TBI, Bulstrode and colleagues69 completed an analysis of mitochondrial (mt) DNA haplogroups, APOE genotype, advancing age and Glasgow Outcome Score data. The mtDNA K haplogroup was positively associated with the 6 month Glasgow Outcome Score (p=0.0008).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is likely that multiple genes influence recovery and susceptibility to brain injury and one cannot study a single genetic polymorphism in isolation. For example, in a study of over 1000 European patients with TBI, Bulstrode and colleagues69 completed an analysis of mitochondrial (mt) DNA haplogroups, APOE genotype, advancing age and Glasgow Outcome Score data. The mtDNA K haplogroup was positively associated with the 6 month Glasgow Outcome Score (p=0.0008).…”
Section: Discussionmentioning
confidence: 99%
“…According to the cited study, the effects of carriership of haplogroup K were independent from the effects of carriership of APOE4. Generally, carriership of APOE4 is associated with poorer outcomes after brain injury, but carriership DNA repair capacity-a factor in late-onset dementia of mitochondrial DNA of haplogroup K apparently neutralised the effects of APOE4 [113]. Haplogroups K and the closely related haplogroup U were demonstrated to have a protective effect against AD in European populations [114].…”
Section: Breath Of Life (And Death) -Increased Atp Production Is Assomentioning
confidence: 99%
“…Carriership of haplogroup K (common in Western Europe and the British Islands) may protect against transient ischaemic attack and ischemic stroke [112]. In individuals with traumatic brain injury carriership of mitochondrial DNA of haplogroup K was associated with significantly better outcomes 6 months after the injury [113]. According to the cited study, the effects of carriership of haplogroup K were independent from the effects of carriership of APOE4.…”
Section: Breath Of Life (And Death) -Increased Atp Production Is Assomentioning
confidence: 99%
“…In this vein, different mtDNA haplgroups have been implicated in playing a role in TBI outcome in a number of studies. A population study conducted in England showed that mtDNA has a significant association with TBI outcomes, as certain haplogroups (K and T) have strong protective effect in TBI [15]. Another study reported that there is a strong correlation between mtDNA deletions in patients of acute brain injury [64].…”
Section: Mitoepigeneticsmentioning
confidence: 99%